Ion transport behavior in polymerized imidazolium ionic liquids incorporating flexible pendant groups - Lee, Jin Hong; Lee, Je Seung; Lee, Jang-Woo; Hong, Soon Man; Koo, Chong Min (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
A series of polyvinylimidazolium cations containing an ethyl, mono, or triethylene oxide pendant groups with [TFSI](-) anion as counterion were synthesized via radical polymerization. The physical properties and ion conduction behaviors of the polymerized ionic liquids (PILs) were investigated to elucidate the effects of ethylene oxide unit. As the length of the ethylene oxide pendant group in the PILs increased, the glass transition temperature of PIL decreased and the ionic conductivity increased, implying that the introduction of ethylene oxide pendant group on the imidazolium cation improved the chain mobility of the resulting polymer macromolecules. When an equimolar amount of LiTFSI to the ionic groups in the PIL was added, the ionic conductivities were further enhanced up to 3 x 10(-5) S cm(-1) at room temperature. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: GEL ELECTROLYTES; MOLTEN-SALTS; MONOMERS